The Level Of Health Awareness And Its Reflection On Body Mass Index Among University Students - Abdelkoui , Rachid (sports creativity, 2025)
The aim of this study was to find out the level of Health Awareness among university students, and to identify differences according to the variable of body mass index (BMI). The study was conducted on a sample of student-athletes (475 female and male students from the University of Djilali Bounaama, Khemis Miliana – Algeria) selected randomly. A Descriptive survey research method was used. A measurement tool to assess health awareness consisted of five axis (including nutrition, physical exercise, personal health, mental health, and strength) with 57 items as well as body mass index were applied. In conclusion, the health awareness among students was high. There are statistically significant differences in health awareness according to BMI variable. Further qualitative studies should be conducted to identify potential nutrition and physical exercises issues so that an intervention can be planned at the community to promote students awareness.